2013
DOI: 10.1039/c2cp42369c
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the transition from sequential to concerted electrochemical proton–electron transfer

Abstract: A theory for the calculation of potential energy surfaces of electrochemical protoncoupled electron transfer is considered and parameterized on the basis of thermodynamic relations. The paper discusses the qualitatively different potential energy surfaces predicted by the theory, and their relation to the existence of sequential and concerted proton-electron transfer pathways. The concomitant activation energies for sequential and concerted PET are calculated. The applied overpotential may change the qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 61 publications
(103 reference statements)
4
103
0
2
Order By: Relevance
“…The simple kinetic modeling theory presented here builds on previous Hamiltonian modeling [28] and thermodynamic considerations [10]. The modeling confirms the role of pH in optimizing the reactivity of electrocatalytic reactions, leading to volcano-type activity relations if acid-base equilibria are involved in the reaction mechanism.…”
Section: Resultsmentioning
confidence: 88%
“…The simple kinetic modeling theory presented here builds on previous Hamiltonian modeling [28] and thermodynamic considerations [10]. The modeling confirms the role of pH in optimizing the reactivity of electrocatalytic reactions, leading to volcano-type activity relations if acid-base equilibria are involved in the reaction mechanism.…”
Section: Resultsmentioning
confidence: 88%
“…[16][17][18] It is important to elucidate those ORR processes at the atomic level, which may help to identify the rate-determining step of the ORR kinetics and the origin of the overpotential. Early work has suggested as equential reduction of oxygen on various electrode surfaces.…”
Section: Orr Mechanismsmentioning
confidence: 99%
“…8). A theoretical thermodynamic argument has shown that this is a generic feature of sequential proton-electron transfer reactions (AH A − + H + followed by A [36][37][38]. Therefore, the pK a of the molecule of interest is an important factor for predicting the optimal pH for its oxidation.…”
Section: Kinetic Modeling Of Hcooh/hcoo − Oxidationmentioning
confidence: 99%
“…The significance of the present study goes beyond this relatively simple electrocatalytic system because many electrocatalytic reactions are strongly pH dependent and the pH dependence must be related to the decoupling of proton and electron transfer at some stage in the reaction mechanism [36][37][38]. Recently, such an effect was shown to be important for predicting the optimal pH for electrooxidation of alcohols on gold electrodes [39].…”
Section: Introductionmentioning
confidence: 99%